2017
DOI: 10.18535/jmscr/v5i11.188
|View full text |Cite
|
Sign up to set email alerts
|

To Study the Clinical Profile of HIV/AIDS Patients

Abstract: Introduction: The Human Immunodeficiency Virus (HIV) is a lenti virus (a subgroup of retrovirus) that causes HIV infection and acquired immunodeficiency syndrome (AIDS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Similarly, in the study by Dr Dinesh Kumar et al at Jabalpur out of total 269 subjects, 88.55% were in the age group between 20-49 years, 71.7% were educated up to 12 th class and 73.60% were having <836 per capita per month. 5 Kumari et al in their study at Varanasi found that out of 5308 subjects 80.5% of in the age group between 25-49 years, 36.2% were illiterate followed by 34.9% who were educated up to secondary class. 6 In our study sexual route was most common mode of transmission with maximum number of subjects 79.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, in the study by Dr Dinesh Kumar et al at Jabalpur out of total 269 subjects, 88.55% were in the age group between 20-49 years, 71.7% were educated up to 12 th class and 73.60% were having <836 per capita per month. 5 Kumari et al in their study at Varanasi found that out of 5308 subjects 80.5% of in the age group between 25-49 years, 36.2% were illiterate followed by 34.9% who were educated up to secondary class. 6 In our study sexual route was most common mode of transmission with maximum number of subjects 79.…”
Section: Discussionmentioning
confidence: 95%